Epic tomatoes : how to select & grow the best varieties of all time - LeHoullier, Craig (Storey Publishing, 2015)
Savor your best tomato harvest ever! Craig LeHoullier, tomato adviser for Seed Savers Exchange, offers everything a tomato enthusiast needs to know about growing more than 200 varieties of tomatoes--from sowing seeds and planting to cultivating and collecting seeds at the end of the season. He also offers a comprehensive guide to the various pests and diseases of tomatoes and explains how best to avoid them.